Criminalization of Voluntary Incest Among Adults in Comparative Perspective - Sajaia, Tamta (European Scientific Journal, ESJ, 2018)
In the present article – “Criminalization of Voluntary Incest Among Adults in Comparative Perspective" - the author fully shares the opinion that prohibition of incest is a major step taken by human beings from their original natural state towards civilization. Intimate relations between blood relatives can destroy the family structure and the whole society. It can ruin the moral principles of the democratic state and serve as a basis for producing genetically abnormal offspring. Consequently, the negative attitude to the "incestuous relations" is universal and well known to the civilization; although, the interpretation of such relations and the social and legal forms of making impact on it are different, thus, the complexity of legislative approaches, revealing the importance of the issue. The definition of incest has been worked out on the basis of: a) formulation of public attitudes toward incest and revealing the main tendencies of the development of the legislation in the historical context; b) comparison of the national legislation with the legislative base of other states worldwide and their legal systems; c) analysis of the practice of the European Court of Human Rights and the scientific research works on related topics. In order to initiate criminalization of voluntary incest among adults, the definitions tailored to the Georgian legislation have been elaborated.